2014
DOI: 10.23986/afsci.8576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of day for harvest and postharvest treatments on the sugar metabolism of broccoli (Brassica oleracea var. italica)

Abstract: Loss of sugars contributes to accelerate postharvest senescence of broccoli. Several treatments have been developed to delay senescence, but in many cases their effects on sugar metabolism were not analyzed. We studied the effect of harvest at different times of day (08:00, 13:00 and 18:00 h) and of several postharvest treatments as heat treatment (HT), modified atmosphere (MA) and 1-methylcylcopropene (1-MCP) on sugar levels and activities of enzymes related to sucrose and starch degradation. Harvesting at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…However, after 5 days of storage, samples collected at afternoon were those with the higher total chlorophyll content. These results were in accordance to those described in a previous works (Hasperué et al, ; Hasperué, Lemoine, Chaves, & Martínez, ).…”
Section: Resultssupporting
confidence: 93%
“…However, after 5 days of storage, samples collected at afternoon were those with the higher total chlorophyll content. These results were in accordance to those described in a previous works (Hasperué et al, ; Hasperué, Lemoine, Chaves, & Martínez, ).…”
Section: Resultssupporting
confidence: 93%
“…Róth et al (2007) reported high fructose content in apples representing 55%-70% of total sugars, followed by sucrose and glucose, which behaved similarly to the results presented in this study. Several post-harvest treatments that delay the ageing process also allow the products to maintain higher levels of sugars; however, the presence of saccharolytic enzymes can be associated with a decrease in the sucrose concentration (Hasperué et al 2014). A decline in the concentration of sucrose accompanied by an increase in the glucose content of apples could be explained by the activity of saccharolytic enzymes such as neutral and vacuolar invertase (Zhu et al 2013).…”
Section: Sugar Profilementioning
confidence: 98%
“…In broccoli, changes in the metabolism due to time of day for harvest influenced the expression of genes during the day and also caused different patterns of expression during postharvest (Hasperué et al, 2013). Harvesting at the end of day maintained the green color of the inflorescence and the sugar levels of broccoli during postharvest (Hasperué et al, 2014). In lettuce, Moccia et al (1998) reported that the postharvest quality of several lettuce cultivars is affected by time of day for harvest and the best time appeared to be variable depending on the variety.…”
Section: Introductionmentioning
confidence: 97%
“…The quality and postharvest shelf life of baby spinach can be affected by a range of pre-harvest factors such as genotype, maturity stage, growing conditions and proper harvesting time (Howard et al, 2002;Clarkson et al, 2005;Pandjaitan et al, 2005;Conte et al, 2008;Chang et al, 2013). In particular, the time of day for harvest has been reported to influence quality and the composition of bioactive compounds of fresh products (Khalid et al, 2009;Moghaddam et al, 2013;Hasperué et al, 2013Hasperué et al, , 2014. In baby leaves, significant improvements to postharvest shelf life have been described as being achieved by rescheduling the time of day for harvest to end-of-day harvest (Clarkson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%